Mozart - Wenborn, Neil (Simon & Schuster, 1994)
This unique combination of book and CD is the perfect introduction to the life and works of Mozart. Accompanying the illustrated biography are a complete list of works with recommended recordings It is the ideal companion to every compact disc collection.